2015
DOI: 10.1186/s13054-015-0796-x
|View full text |Cite
|
Sign up to set email alerts
|

An ADAM10 promoter polymorphism is a functional variant in severe sepsis patients and confers susceptibility to the development of sepsis

Abstract: IntroductionAlthough genetic variants of the A disintegrin and metalloproteinase 10 (ADAM10) gene have been shown to be associated with susceptibility to several inflammatory-related diseases, to date little is known about the clinical relationship in the development of sepsis.MethodsTwo genetic variants in the promoter of ADAM10 were selected to analyze the potential association with the risk of sepsis. A total of 440 sepsis patients and 450 matched healthy individuals in two independent Chinese Han populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 45 publications
3
38
0
2
Order By: Relevance
“…Indeed, there is literature regarding the putative AT receptor ADAM10. Analysis of ADAM10 polymorphisms in human sepsis revealed that the C allele of rs653765 ADAM10 promoter conferred susceptibility to the most severe septic episodes due to increased ADAM10 levels (Cui et al, 2015). In addition, we observed that AT and S. aureus culture supernatant induced rapid human platelet aggregation that was inhibited by MEDI4893*.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is literature regarding the putative AT receptor ADAM10. Analysis of ADAM10 polymorphisms in human sepsis revealed that the C allele of rs653765 ADAM10 promoter conferred susceptibility to the most severe septic episodes due to increased ADAM10 levels (Cui et al, 2015). In addition, we observed that AT and S. aureus culture supernatant induced rapid human platelet aggregation that was inhibited by MEDI4893*.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rs653765 polymorphism may be a functional SNP because the rs653765 C > T polymorphism is located one base downstream of the potential site for the myc-associated zinc finger protein (MAZ) transcription factor 16. The ADAM10 rs653765 polymorphism was also associated with the development of severe sepsis 17; however, the risk CC genotype was suggested to have functionally affected the expression level of ADAM10 mRNA, which was accompanied by the upregulation of its substrates 17, compared with the “GA + AA” genotype in HCC being associated with a higher risk of distant metastasis in the present study (Table 4). Although the functions and detailed mechanisms of ADAM10 rs514049 remain uncertain and controversial, rs514049 and rs653765 are involved in HCC disease progression and metastasis, and rs653765 may play a more essential role in regulating ADAM10 expression in HCC and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous of studies have demonstrated that several functional genetic variations in the genes encoding RAGE, ADAM10 and TNF-α may influence the risk and development of sepsis [32][33][34][35]. However, to the best of our knowledge, the genetic variations of ADAM17 have not been determined in patients with sepsis, adequately.…”
Section: Introductionmentioning
confidence: 95%